Heritage as a scenery: dubrovnik or king’s landing? - Durán Rocca, Luisa (Universidad Nacional del Litoral, 2021)
The present work studies the effects of the usage of cultural heritage of historical cities as scenery of media products. We present a case study of the Old City of Dubrovnik, which is located in the south of Croatia. The City was inscribed on the UNESCO World Heritage List in 1979 for representing a masterpiece of humanity. This recognition has brought prestige and exposure at international level increasing the tourist interest. However, recently, the Old City has been affected by the impact of mass tourism generated by being the location of the TV show Game of Thrones (2011-2019). With the exhibition of the show, the number of visitors has grown and continues to grow, jeopardizing the heritage values. We find that while physical components of the Old City are in acceptable condition, the activities resulting from mass visitation are factors of degradation and have been altering the urban landscape. We conclude that, in addition to efficient management to discipline visitation and the implementation of programs to preserve the heritage, interpretation and heritage education actions are needed, which reconcile the relationship between residents and tourists, and recover the balance between the authenticity of the place and the expectations of visitors.